South Caucasian river monitoring database management applying GIS technology - Amirkhanyan, M. (Mathematical Problems of Computer Science, 2021)
The article is devoted to river monitoring data collection and processing and their presentation as electronic maps. For such a purpose, ArcView GIS program was applied which is an innovative technology of data integration. It is shown how to expand program possibilities for the solution of stated problems.